Development of Caecum in Prenatal Goat (Capra hircus): A Histological Perspective - Abhinov Verma; MM Farooqui; Ajay Prakash; Archana Pathak; Shriprakash Singh; Anand Singh; Rupam Sinha (Indian Journal of Veterinary Anatomy, 2024)
The aim of this study was to observe sequential developmental changes of caecum from its primordial stage upto parturition. For this purpose, the study was conducted on the caecum of 36 goat foeti divided into 03 groups and each group was comprised of 12 foeti. The sections of caecum were stained for general histoarchitecuture and connective tissue fibres. The transformation of stratified to simple columnar epithelium began at 66 days and completed on 75 days of gestation. The villi were identified first time at 58 days of gestation and villi degeneration started at 97 days of gestation and was indistinct near term. The typical goblet cells were noticed at 107 days of gestation. The formation of enteric nervous system (submucosal plexus) witnessed first time at 58th day of gestation in propria submucosa while at 82th days of gestation in tunica muscluaris (myeteric plexus). The connective tissue fibers viz. reticular, collagen and elastic were evident at 45, 104 and 150 days of gestation, respectively. The differentiating inner circular myocytes were noticed at 45th days of gestation while the outer longitudinal myocyte layers were evident first time at 50th day of gestation. The statistical analysis showed continuous increase in the thickness of all stratum of the wall of caecum except thickness of epithelium which was decreased as age of gestation advanced.